Pengaruh Perceived Organizational Support dan Work Engagement Terhadap Kinerja Karyawan Selama Masa Pandemi Covid 19 - Jumrotul Hafifah; Maslichah Maslichah; Dwiyani Sudaryanti (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This study aims to determine whether perceived organizational support and work engagement affect employee performance during the pandemic for MSME actors, whether perceived organizational support influences employee performance during the pandemic for MSME actors, and whether work engagement affects employee performance during the pandemic. to SMEs. This research was conducted on SMEs located in Malang City, using a purposive sampling method and the number of respondents was 140 respondents. The analysis technique used is a partial test (t). Based on the results of hypothesis testing that has been carried out by researchers, the conclusions are as follows: Based on the results of simultaneous testing that the variables perceived organization support (X1) and work engagement (X2) have a simultaneous effect on employee performance (Y). Based on the partial test results, that the variable perceived organizational support (X1) has a significant effect on employee performance (Y). Based on the results of hypothesis testing, that the work engagement variable (X2) has a significant effect on employee performance Keywords: Employee Performance, perceived organizational support, and work engagement